Incentive effects in tournaments with heterogeneous competitors: An analysis of the Olympic Rowing Regatta in Sydney 2000 - Norbert Bach; Oliver Gürtler; Joachim Prinz (Management Revue, 2009)
A large part of the theoretical tournament literature argues that rank-order tournaments only unfold their incentive effects if the contestants all have similar prospects of winning. In heterogeneous fields, the outcome of the tournament is relatively clear and the contestants reduce their effort. However, empirical evidence for this so-called contamination hypothesis is sparse. An analysis of 442 showings at the Olympic Rowing Regatta in Sydney 2000 gives evidence that oarsmen spare effort in heterogeneous heats. This implies that competition among staffs with heterogeneous skill levels does not bring about the intended effort levels. However, a separate subgroup analysis shows that only the tournament favourites hold back effort whereas underdogs bring out their best when competing against dominant rivals. A heterogeneous tournament could then be enriched by absolute performance standards to increase incentives of the favourites.
Keywords: 650; tournaments; heterogeneity; incentive effects; effort